Control of doubly fed induction generator using internal model control method - Ho, Anh Vu; Duong, Hoai Nghia (Journal of Technical Education Science, 2010)
In this paper, we develop an internal model controller (IMC) for a doubly fed induction generator (DFIG). The plant is represented in the stator d-q reference frame and is a linear time-varying system. The main advantage of the proposed IMC controller is that it allows to specify the transfer function of the closed-loop system as well as the trade-off between the performance and the robustness of the control system. Simulation results are provided for illustration.